The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1111/j.1745-6584.2003.tb02436.x
|View full text |Cite
|
Sign up to set email alerts
|

Ground Water Occurrence and Contributions to Streamflow in an Alpine Catchment, Colorado Front Range

Abstract: Ground water occurrence, movement, and its contribution to streamflow were investigated in Loch Vale, an alpine catchment in the Front Range of the Colorado Rocky Mountains. Hydrogeomorphologic mapping, seismic refraction measurements, and porosity and permeability estimates indicate that talus slopes are the primary ground water reservoir, with a maximum storage capacity that is equal to, or greater than, total annual discharge from the basin (5.4 ± 0.8 × 106 m3). Although snowmelt and glacial melt provide th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
203
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(223 citation statements)
references
References 28 publications
11
203
1
Order By: Relevance
“…Snowpack amounts have already declined in much of the western United States since the 1950s, and snowmelt occurs more than 20 days earlier than in the late 1940s due to moderate warming trends (Stewart et al, 2004). Air temperatures have increased 1.1-1.4 8C since the early 1990s in the Loch Vale Watershed of Rocky Mountain National Park, although this is mostly a summer phenomenon, and has not influenced winter snow dynamics (Clow et al, 2003). Climate change scenarios project warmer temperatures throughout the year, and either increasing winter precipitation or similar precipitation patterns to those observed currently (Smith et al, 2000).…”
Section: Nonlinear Responses In Rocky Mountain Aquatic Ecosystems Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Snowpack amounts have already declined in much of the western United States since the 1950s, and snowmelt occurs more than 20 days earlier than in the late 1940s due to moderate warming trends (Stewart et al, 2004). Air temperatures have increased 1.1-1.4 8C since the early 1990s in the Loch Vale Watershed of Rocky Mountain National Park, although this is mostly a summer phenomenon, and has not influenced winter snow dynamics (Clow et al, 2003). Climate change scenarios project warmer temperatures throughout the year, and either increasing winter precipitation or similar precipitation patterns to those observed currently (Smith et al, 2000).…”
Section: Nonlinear Responses In Rocky Mountain Aquatic Ecosystems Tomentioning
confidence: 99%
“…Both soil moisture and runoff increased 4-5 weeks earlier than the mean onset of spring conditions from 1984 to 1998 (Baron et al, 2000a,b). There are long-term implications of earlier snow melt and increased warming for permafrost; Clow et al (2003) project that increased air temperatures are sufficient to raise low elevation permafrost and rock glaciers by 150-190 m, leading to a short-term increase in streamflow. The long-term implications of permafrost melting include highly nonlinear stream flows, including late summer stream drying.…”
Section: Nonlinear Responses In Rocky Mountain Aquatic Ecosystems Tomentioning
confidence: 99%
“…Mountainous and, in particular, alpine groundwater is contributing significantly to the stream flow of rivers in valleys and consequently in the foreland (e.g., Campbell et al 1995;Clow et al 2003;Tague and Grant 2009;Muir et al 2011;Welch et al 2012). With increasing population and propagation of tourist industries and recreational activities in mountainous areas, knowledge of the hydraulic behavior and storage capacities of mountainous aquifers is getting more important for sustainable water resources management as well as for predicting natural hazards, as for example flash floods and debris flows (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While the hydrogeology of moraines, talus and hillslope aquifers has been the subject of intensive investigations (e.g., Clow et al 2003;Roy and Hayashi 2009;Muir et al 2011), knowledge about the hydraulic behavior and storage capacities of rock glaciers is sparse (Krainer and Mostler 2002;Krainer et al 2007;Millar et al 2013;Winkler et al 2016a). Nevertheless, rock glaciers are common landforms all around the globe in mountainous areas and at high latitudes-for instance, in the Austrian Alps, KellererPirklbauer et al (2012) and Krainer and Ribis (2012) have identified a total of 4,792 rock glaciers covering an area of about 286 km 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Most snowmelt and rainfall in the Andrews basin flows through shallow subsurface flow paths to the alpine stream. These flow paths regulate the export of other chemical constituents (Campbell et al, 1995;Clow et al, 2003), and likely explain why such a high percentage of the Hg input is retained, despite thin, patchy soil cover.…”
mentioning
confidence: 99%